Dampak Jaminan Fidusia Kredit Kendaraan Bermotor yang Tidak Didaftarkan terhadap Penerimaan Negara Bukan Pajak - Akhmad Yasin (Jurnal Konstitusi, 2020)
Motor vehicles ownership through finance companies can be realized after going through a series of procedures before a notary and fiduciary registration office. However, this series of procedures are not done by finance companies in providing motor vehicle financing to consumers. Increasing consumer financing to the public for motor vehicles ownership should also increase the number of non-tax state revenues from fiduciary guarantees. The study purpose is to know the legal consequences for fiduciary recipients who did not register their fiduciary guarantees and to know the impact of unregistered fiduciary guarantees on non-tax state revenue (PNBP). The formulation of the problem in the research question is how the legal consequences for fiduciary recipients who do not register their fiduciary guarantees and how the impact of unregistered fiduciary guarantees on non-tax state revenue (PNBP). The research method used is descriptive qualitative normative legal research using secondary data. The study results found that fiduciary finance companies/ recipients did not register their fiduciary guarantee, so they committed illegal acts by utilizing third parties to execute motorized vehicles that were not actually burdened with fiduciary guarantees. The executor’s right to fiduciary recipient is legally flawed because he does not hold a fiduciary guarantee certificate as a result of not registering a motorized vehicle as a fiduciary guarantee. The impact on state finances because they were not registering motor vehicles as fiduciary guarantees at the fiduciary registration office resulting in non-tax revenue (PNBP) being not optimal for the state.